Clinical Relevance and Prognostic Value of the Neuronal Protein Neuroligin 2 in Breast Cancer - Zhang, Gang; Sun, Yi; Wu, Zheng-sheng; Huang, Xing (Frontiers in Oncology, 2021)
Neuroligin 2 (NLGN2) is a well-recognized transmembrane scaffolding protein that functions in synapse development and neuronal signal transduction. It has recently been implicated in multiple diseases of peripheral ectodermal origin. However, the potential roles of NLGN2 in tumors remain ill-defined. The aim of this study was to determine the clinical relevance and prognostic value of NLGN2 in breast cancer. To this end, breast cancer datasets were extracted from TCGA and other public databases, and subjected to Kaplan-Meier potter for survival analysis, GEPIA2 for assessing the immunological relevance of NLGN2 and THPA for identifying its subcellular localization. The in-silico results were further validated by immunohistochemistry analysis of in-house tumor tissue specimens. NLGN2 was identified as a prognostic factor in breast cancer subtypes, and its high expression correlated to a favorable survival outcome. Moreover, NLGN2 overexpression in breast cancer was significantly associated with large tumor size, lymph node metastasis, late TNM stage, and high histological grade. Interestingly, there was a significant correlation between the expression level of NLGN2 and the immunomodulatory molecules, along with increased interstitial infiltration of lymphocytes. Furthermore, NLGN2 was predominantly localized in the mitochondria of breast cancer cells. In conclusion, NLGN2 has a prognostic role and immunoregulatory potential in breast cancer, and its functions likely have a mitochondrial basis. It is a promising therapeutic target in breast cancer and should be explored further.